2017
DOI: 10.1186/s12958-017-0308-8
|View full text |Cite
|
Sign up to set email alerts
|

Making gametes from alternate sources of stem cells: past, present and future

Abstract: Infertile couples including cancer survivors stand to benefit from gametes differentiated from embryonic or induced pluripotent stem (ES/iPS) cells. It remains challenging to convert human ES/iPS cells into primordial germ-like cells (PGCLCs) en route to obtaining gametes. Considerable success was achieved in 2016 to obtain fertile offspring starting with mouse ES/iPS cells, however the specification of human ES/iPS cells into PGCLCs in vitro is still not achieved. Human ES cells will not yield patient-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 144 publications
1
41
0
1
Order By: Relevance
“…More importantly, under conditions like organ damage, activated VSELs can contribute to the regeneration of damaged organ tissues by their mobilization in peripheral blood [99]. Due to their detection in PGCs, gonadal tissue (both functional and non-functional), and ability to survive oncotherapy (due to quiescent nature), VSELs have been given preference for the development of gametes in vitro [45,100]. Adult mammalian ovaries not only acts as reservoirs for oocytes but also have the presence of other valuable stem cell sources such as OSCs and VSELs.…”
Section: Very Small Embryonic-like Stem Cells (Vsels): New Heroes In mentioning
confidence: 99%
“…More importantly, under conditions like organ damage, activated VSELs can contribute to the regeneration of damaged organ tissues by their mobilization in peripheral blood [99]. Due to their detection in PGCs, gonadal tissue (both functional and non-functional), and ability to survive oncotherapy (due to quiescent nature), VSELs have been given preference for the development of gametes in vitro [45,100]. Adult mammalian ovaries not only acts as reservoirs for oocytes but also have the presence of other valuable stem cell sources such as OSCs and VSELs.…”
Section: Very Small Embryonic-like Stem Cells (Vsels): New Heroes In mentioning
confidence: 99%
“…Production of germ cells from stem cells is a very interesting and promising area in the field of reproductive medicine. It has been shown that stem cells derived from different regions, such as menstrual blood, amniotic fluid, lung, skin and pancreas, have the capacity to differentiate into germ cell-like cells [ 22 , 23 , 24 ]. MSCs can be isolated from various sources especial from neonatal tissues, such as placenta, umbilical cord and Wharton's jelly may offer certain advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers found that there exists a novel population of pluripotent stem cells termed very small embryonic-like stem cells (VSELs) in the testes which can survive chemotherapy. Mesenchymal cells or Sertoli cells transplanted into busulfan-treated testes could secret some paracrine factors to restore healthy stem niche and support surviving VSELs to undergo spermatogenesis [ 56 , 57 ]. Surprisingly, our study showed that SSCLCs could restore the spermatogenesis of busulfan-treated recipient mice (Fig.…”
Section: Discussionmentioning
confidence: 99%